Bidirectional relationships between phonological processing and basic number knowledge in kindergarten children: a longitudinal study - Xin Chen; Chi Ma; Zihan Yang; Xiujie Yang (BMC Psychology)
Abstract An ongoing debate on the association between phonological processing and number knowledge concerns the extent to which they influence each other during early childhood. The current study aims to establish the direction of the developmental relationship between these two kinds of abilities at an early age. Eighty-two Chinese kindergarten children were followed from 5 to 6 years old with a one-year interval. We investigated three phonological processing skills (phonological awareness, phonological memory, and rapid automatized naming) and two kinds of basic number knowledge (number identification and number comparison) at time 1 and time 2. Cross-lagged panel analyses revealed that the association between phonological awareness and number comparison was bidirectional. Specifically, early phonological awareness at time 1 could predict later number identification, and early number comparison at time 1 was a significant predictor of later phonological memory. In contrast, rapid automatized naming had no such predictive relations with other variables. The present findings are among the first to provide evidence that basic number knowledge could predict later phonological processing in kindergarten children.